CHEST COMPRESSION WORKSHOP BASED ON RULE OF FIVE ON DEPTH AND CHEST COMPRESSION FREQUENCY AT THE GRANDMED HOSPITAL IN 2022: CHEST COMPRESSION WORKSHOP BASED ON RULE OF FIVE ON DEPTH AND CHEST COMPRESSION FREQUENCY AT THE GRANDMED HOSPITAL IN 2022 - Purba, Anita Gandaria; Syara, Arfah May; Yanti, Dian Anggri; Harahap, Miftahul Jannah; Arisman, Yessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Several measures to maintain life in cardiac arrest according to the American Heart, namely the application of a chain of survival, namely first aid when cardiac arrest occurs until treatment afterward. The rule of five is a rhythm calculation technique in chest compressions using the numbers 1,2,3,4,5, and 6 which adopts only 2 syllables. The purpose of this community service is to determine the ability of nurses to perform chest compressions based on the rule of five on the depth and frequency of chest compressions at Grandmed Hospital, Lubuk Pakam District, Deli Serdang Regency. The results of community service before being given a workshop show that nurses who perform chest compressions based on the rule of five to patients, namely all respondents have different percentage levels, namely good category as many as 7 people (23.3%), sufficient category as many as 14 people (46.7% ), and the less category as many as 9 people (30%). While the results obtained after being given a workshop show that nurses who perform chest compressions based on the rule of five to patients, namely all respondents have an increase in different percentage levels, namely the good category as many as 17 people (56.7%), the sufficient category as many as 9 people (30%), and the less category as many as 4 people (13,3%). The chest compression calculation system applied is the rhythm calculation system, namely and one, and two, and three, and four. If chest compressions are carried out properly and correctly according to the rules, compression pauses and consistency will create good tissue perfusion.